2020
DOI: 10.21203/rs.3.rs-26517/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disruption of the CCL5/RANTES-CCR5 Pathway Restores Immune Homeostasis and Reduces Plasma Viral Load in Critical COVID-19

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of coronavirus disease 2019 (COVID-19), is now pandemic with nearly three million cases reported to date1. Although the majority of COVID-19 patients experience only mild or moderate symptoms, a subset will progress to severe disease with pneumonia and acute respiratory distress syndrome (ARDS) requiring mechanical ventilation2. Emerging results indicate a dysregulated immune response characterized by runaway inflammation, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Due to its immune system restorative properties, leronlimab is being investigated for compassionate use in the treatment of COVID-19 patients [96,97]. Studies examining receptor blockade in leronlimab preliminarily have shown decreases in IL-6, restoration of CD4/CD8 ratios, and reduction in overall COVID-19 viremia [98]. These collective findings suggest possible therapeutic role in establishing immune reconstitution in patients that are critically ill and may provide dual benefit in patients with shared cancer diagnoses.…”
Section: Potential Overlapping Mechanisms In Covid-19 and Cardiovascumentioning
confidence: 99%
“…Due to its immune system restorative properties, leronlimab is being investigated for compassionate use in the treatment of COVID-19 patients [96,97]. Studies examining receptor blockade in leronlimab preliminarily have shown decreases in IL-6, restoration of CD4/CD8 ratios, and reduction in overall COVID-19 viremia [98]. These collective findings suggest possible therapeutic role in establishing immune reconstitution in patients that are critically ill and may provide dual benefit in patients with shared cancer diagnoses.…”
Section: Potential Overlapping Mechanisms In Covid-19 and Cardiovascumentioning
confidence: 99%
“…PRO 140 has shown a promising antiviral potency with a high barrier to resistance and encouraging shortterm safety and tolerability [189]. A recently published Preprint suggested that leronlimab disrupts the CCL5/ RANTES-CCR5 axis and restores immune homeostasis in COVID-19 patients [133]. The authors observed a marked CCR5 receptor occupancy on macrophages and T lymphocytes, rapid drop of circulating IL-6, CD4/ CD8 ratio restoration and a significant decrease of patients' viremia [133].…”
Section: Leronlimabmentioning
confidence: 99%
“…A recently published Preprint suggested that leronlimab disrupts the CCL5/ RANTES-CCR5 axis and restores immune homeostasis in COVID-19 patients [133]. The authors observed a marked CCR5 receptor occupancy on macrophages and T lymphocytes, rapid drop of circulating IL-6, CD4/ CD8 ratio restoration and a significant decrease of patients' viremia [133]. These encouraging findings boosted the rapid entrance of leronlimab into two clinical trials for mild to moderate and severe COVID-19 infection (NCT04343651 and NCT04347239).…”
Section: Leronlimabmentioning
confidence: 99%